Research on peak power test method for Lithium Ion battery - Shen, Xiaofeng; Sun, Bingxiang; Qi, Hongfeng; Shen, Xiaobo; Su, Xiaojia (Energy procedia, 2018)
The peak power of the battery (SOP) is an important parameter index for electric vehicle to improve the efficiency of battery utilization and ensure the safety of the system in the maximum limit. The estimation and prediction of SOP is based on a large number of test data at different temperature, different SOC and different time scales. It is important to improve SOP test efficiency under the premise of guaranteeing accuracy, which is also significant for BMS algorithm design and development investment reduction. In this paper, with 2.75Ah ternary Li-ion battery as the research object, the test efficiency and accuracy of the current peak power test methods (HPPC, JEVS and constant current charge and discharge ) are compared at different temperatures, through optimizing the JEVS, the test results meet the requirements at different time scales on the basis of high efficiency test, and the optimized JEVS method is verified. The experimental results indicate that the optimized JEVS can accurately estimate the peak power of the battery at different temperatures and greatly shorten the test time.